Intertemporal consumption and debt aversion: A replication and extension - Steffen Ahrens; Ciril Bosch-Rosa; Thomas Meissner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We replicate Meissner (2016) where debt aversion was reported for the first time in an intertemporal consumption and saving problem. While Meissner (2016) uses a German sample, our subjects are US undergraduate students. All of the main findings from the original study replicate with similar effect sizes. Additionally, we extend the original analysis by correlating a new individual index of debt aversion on individual characteristics such as gender, cognitive ability, and risk aversion. The findings suggest that gender and risk aversion are not correlated with debt aversion. However, cognitive ability is positively correlated with debt aversion. Overall, this paper confirms the importance of debt aversion in intertemporal consumption problems and validates the approach of Meissner (2016).
Keywords: C91; D84; G11; G41; 330; Debt Aversion; Replication; Experiment